Innovating hortatory exposition texts: Integrating Pancasila profile and sigil flip story in Indonesian vocational education - Anggraeni Gunawati; Luky Tiasari; Godlove Elioth Kiswaga (Journal of English Language and Pedagogy, 2025)
The integration of technology with the MERDEKA Curriculum and the Pancasila Student Profile is essential for strengthening English learning in Indonesian vocational education. This study aims to: (1) identify the English listening and speaking needs of culinary students; (2) develop hortatory exposition texts that integrate the Pancasila Student Profile through the Sigil‑Flip Story technique; and (3) evaluate the appropriateness of the developed materials. Employing Borg and Gall’s R&D model, the research was limited to four stages: needs analysis, planning, material development, and expert validation. The participants were eleventh-grade culinary students at SMK Muhammadiyah 4 Yogyakarta. Data were collected through observation, interviews, and documentation. The resulting materials three instructional units supported by videos embed the Pancasila Student Profile values. Validation by two experts confirmed that the materials are appropriate for the target learners. The findings indicate that the hortatory exposition texts not only address the students’ specific needs but also align with curriculum standards, effectively integrating the Pancasila Student Profile into vocational English learning.